Leptin Receptor Overlapping Transcript (LEPROT) Is Associated with the Tumor Microenvironment and a Prognostic Predictor in Pan-Cancer - Li, Bingsheng; He, Yao; Li, Pan; Chen, Xiang (Frontiers in Genetics, 2021)
Background: Leptin receptor overlapping transcript (LEPROT) has been reported to be involved in metabolism regulation and energy balance, as well as molecular signalings of breast cancer and osteosarcoma. LEPROT is expressed in various tissue and has been suggested to be involved in cancer developments but with contradictory roles. The comprehensive knowledge of the effects of LEPROT on cancer development and progression across pan-cancer is still missing. Methods: The expressions of LEPROT in cancers were compared with corresponding normal tissues across 33 cancer types. The relationships between expression and methylation of LEPROT were then demonstrated. The correlations of LEPROT with the tumor microenvironment (TME) including immune checkpoints, tumor immune cells infiltration (TII), and cancer-associated fibroblasts (CAFs) was also investigated. Co-expression analyses and functional enrichments were conducted to suggest the most relevant genes and the mechanisms of the effects in cancers for LEPROT. Finally, the correlations of LEPROT with patient survival and immunotherapy response were explored. Results: LEPROT expression was found to be significantly aberrant in 15/33 (45.5%) cancers compared with corresponding normal tissues, in which LEPROT was up-regulated in 12 cancers and was down-regulated in 3 cancers. LEPROT expressions were overall negatively correlated with its methylation alterations. Moreover, LEPROT was profoundly correlated with the TME, including immune checkpoints, TIIs, and CAFs. According to co-expression analyses and functional enrichments, the interactions of LEPROT with the tumor microenvironment may be mediated by the interleukin 6 signal transducer/the Janus kinase/signal transducers and activators of transcription signaling pathway. Prognostic values may exist for LEPROT to predict patient survival and immunotherapy response in a context-dependent way. Conclusions: LEPROT affects cancer development by interfering with the TME and regulating inflammatory or immune signals. LEPROT may also serve as a potential prognostic marker or a target in cancer therapy. This is the first study to investigate the roles of LEPROT across pan-cancer.